The ingroup projection model - Waldzus, S. (Intergroup relations: The role of motivation and emotion, 2009)
Sometimes we do not like a certain group of people. We simply cannot stand them. They did not do anything particular to us. The problem is rather that they are what they are: Diﬀerent. In 1999, Mummendey and Wenzel (1999) presented an approach that tries to explain intergroup conﬂict by means of an analysis of our evaluative response towards outgroups that are diﬀerent from us. Their theoretical framework, which has become known as the “Ingroup Projection Model”, integrates three old themes in social psychology: Selfrelevance of social categorization and psychological group formation (Allport, 1954; Tajfel & Forgas, 1981; Turner, 1987), the notion of prototypicality in intra-category diﬀerentiation (Rosch, 1978), and social projection (Allport, 1924; Krueger, 2007). Based on this analysis, they developed ideas on how to overcome intergroup conﬂict without abandoning intergroup diﬀerences by creating a context in which diﬀerent groups may be able to respect or at least tolerate each other. Since then, much empirical research has been done that supports their ideas, and which has also inspired several theoretical advancements and elaborations of the original approach.